2017
DOI: 10.21608/jfds.2017.38890
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Propolis Extract as A Natural Preservative in Raw Milk

Abstract: Natural antimicrobials have been considered of more importance due to their increase concerns among chemical preservatives among consumers. The effect on the quality of raw milk sample by different concentrations of propolis (5, 10 and20%) in water extract (WEP), stored at 30°C and 5±1°C was evaluated. pH value, titratable acidity and microbiological examination were detected. The addition of 2% water extract of propolis (20% extract) to raw milk resulted in acceptability of the milk up to 12 and 48 hours at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…The antiradical mechanisms of antioxidant peptides was investigated by Esfandi et al (2019) , who cleared the mechanisms include electron donation or transfer proton, these mechanisms may act together, or one dominated depended on peptides structure, wherein the aromatic amino acids make radicals stable by donating electron besides, acidic and essential amino acids act as metal ion chelators, also, the antioxidant activity of milk may be explained by Jakobek, 2015 , Rawel and Rohn, 2010 who mentioned that phenolic compounds might interact with added protein isolates to increase the antioxidant and antibacterial activity, the interaction may occur between OH of phenolic compounds and SH and OH side chains in peptides or protein, protein–phenolic interaction may affect the physicochemical properties of protein and phenolic compounds, the complex may increase the peptide activity through blocking some amino acid side chains, besides, increasing the bioavailability and activity of polyphenols. In a previous study, Cottica et al, 2015 , El-Deeb, 2017 reported that the antioxidant potential of milk increased with propolis extract. The presence of phenolic compounds in dairy products protects other antioxidant ingredients as their resistant to thermal treatments.…”
Section: Discussionmentioning
confidence: 92%
“…The antiradical mechanisms of antioxidant peptides was investigated by Esfandi et al (2019) , who cleared the mechanisms include electron donation or transfer proton, these mechanisms may act together, or one dominated depended on peptides structure, wherein the aromatic amino acids make radicals stable by donating electron besides, acidic and essential amino acids act as metal ion chelators, also, the antioxidant activity of milk may be explained by Jakobek, 2015 , Rawel and Rohn, 2010 who mentioned that phenolic compounds might interact with added protein isolates to increase the antioxidant and antibacterial activity, the interaction may occur between OH of phenolic compounds and SH and OH side chains in peptides or protein, protein–phenolic interaction may affect the physicochemical properties of protein and phenolic compounds, the complex may increase the peptide activity through blocking some amino acid side chains, besides, increasing the bioavailability and activity of polyphenols. In a previous study, Cottica et al, 2015 , El-Deeb, 2017 reported that the antioxidant potential of milk increased with propolis extract. The presence of phenolic compounds in dairy products protects other antioxidant ingredients as their resistant to thermal treatments.…”
Section: Discussionmentioning
confidence: 92%
“…This is probably caused by the antimicrobial effect of pollen on S. thermophilus and L. bulgaricus, leading to a harmful effect on lactic acid bacteria [45]. On the other hand, the propolis extract in raw milk resulted in significantly high acidity values, which could be attributed to the improvement of lactic acid bacteria action, leading to a greater decomposition of sugars in the milk and an increase in acidity [28]. Numerous studies concluded that honey generates changes in total soluble solid content when it is added to dairy products [14,16,17,24].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…El-Deeb [11] reported that four different concentrations of propolis were supplemented to buffalo milk, but the pH was all equal at 6.77 to 6.80. The pH of the yoghurt sample was almost constant, although it was between 4.5 and 4.6 [11]. Hence, this showed a similar tendency to this experiment.…”
Section: The Ph Of Market Milk Yoghurt and Kefir Supplemented With Pmentioning
confidence: 99%
“…According to "Utilization of propolis extract as a natural preservative in raw milk" by El-Deeb [11], he strongly suggested that this method of preservation could be used to encourage the dairy farming by making possible the collection of more milk of high quality, which in turn is prerequisite for increased manufacture of high quality yoghurt [11].…”
Section: The Organoleptic Testing Of Market Milk Supplemented With Prmentioning
confidence: 99%
See 1 more Smart Citation